Strengthening the Community: Role of Village Health Volunteers - Chanpanit, Pannathat; Wongmanee, Weathaka; Judabood, Narak (Journal of The Royal Thai Army Nurses, 2023)
The Village Health Volunteer are group of strong and helpful health personnel, well-coordinated health teams, the group that is well-trained group in the area so that ,they can work well and have easy access to the community in Urban and Rural. They can encourage the community to change health behaviors in the right direction, even if they are trained or promoted health knowledge and receive a gift in practice. Excellent of Village health volunteer ; Fees, education quota allocation in the Ministry of Public Health, Medical treatment and train fare reduction for example, will be the driving force for such groups to have a gift of motivation and performance to work, which will impact sustainable health promotion policies or plans in communities and studies have demonstrated that village health volunteers can serve as health behavior models, participate in health networking, activities, and participation in public health services networks in family physicians, home visited, and local patient care, and play a role in transmited knowledge and specific skills in care for patients, developing patients and caregivers well, and contributed the development and strengthening of the community.